Regime Capability and Relational Stakes in the Emerging World Order - Aditya, Anand (Journal of Foreign Affairs, 2021)
Against the background of an emerging new world order in the 21st century, this paper offers a conceptual frame on the critical role that regime capability can play in modulating the relational stakes of a country. The text in that context offers the case of Nepal as also a few other countries to assess and explain the role and impact of political stability in enhancing relational dividend as well as the pace of democratisation and development. A three-fold typology of governance regimes-survival, subsistential and self-sustaining-is also presented to validate the arguments. The methodology used here is broadly comparative and empirical using ideas conceptualised to facilitate comparison, explanation and elaboration of the arguments forwarded in the course of discussion.